Melena as an unusual presentation of gastrointestinal stromal tumour, a case report. (2018) - Mulkerrin, G.; Hogan, N.M.; Sheehan, M.; Joyce, M.R.
Highlights: Gastrointestinal Stromal Tumours are a rare tumour of mesenchymal origin, and these tumours tend to be discovered incidentally. Here, we discuss the case of a 57-year-old woman who underwent an emergency laporotomy for worsening occult GI bleed. A 9.1 cm GIST was resected from her distal ileum This occured on a background of two prior presentations of melena over a ten year period. We suggest GIST should be considered as a possible differential in cases of gastrointestinal bleed, where other more common causes have been ruled out. Abstract: Introduction: Gastrointestinal Stromal Tumors (GISTs) are a rare slow growing malignancy, accounting for less than 1% of all gastrointestinal (GI) tract tumors. These tumors are usually discovered incidentally by endoscopy, surgery or radiology. However on occasions they may present with significant symptoms including GI blood loss. This case report discusses an atypical presentation of a GIST in a 57-year-old female. Case presentation: A 57-year-old woman presented to the emergency department following one episode of melena. This occurred on a background of two previous presentations with melena over a 10-year period. She had a preceding surgery for a Meckel's Diverticulum. She was admitted for monitoring and investigation. An emergency upper endoscopy showed no upper gastrointestinal pathology to account for the bleeding. Her condition deteriorated with development of hypovolemic shock, requiring blood transfusion. An urgent CT angiogram identified a large mass in the distal ileum. The patient underwent an emergency laparotomy, where a 9.1 cm tumor located on the distal one-third of the ileum was resected. Histopathology confirmed the mass was a GIST. The patient had a successful post-operative period and subsequent treatment with Imatinib. Discussion: The majority of GISTs are found incidentally. This case report describes an unusual presentation of a GIST in which the tumor bled into the intestinal lumen causing significant melena and life threatening hemorrhage. Conclusion: We conclude that GIST should be considered as a possible differential in rare cases of GI bleeding where more common causes have been ruled out.